2019
DOI: 10.1101/2019.12.20.885244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New Tools for Genetically Targeting Myeloid Populations in the Central Nervous System

Abstract: As the resident macrophages of the brain and spinal cord, microglia are crucial for the phagocytosis of infectious agents, apoptotic cells and synapses. Developmentally, microglia originate from the embryonic yolk sac and serve important roles in the sculpting of neonatal neural circuits. During brain injury or infection, bone-marrow derived macrophages invade neural tissue, making it difficult to distinguish between invading macrophages and resident microglia. In addition to circulation-derived monocytes, oth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Pf4 expression was proposed to reflect platelet/macrophage conjugates. However, several studies in reporter mice driven by Pf4-Cre have demonstrated widespread macrophage expression of this gene, notably in peritoneal macrophages 152 and (peri)vascular macrophages 153 . Thus, Pf4 can no longer be considered platelet-specific.…”
Section: Macrophage Subsets In Atherosclerosismentioning
confidence: 99%
“…Pf4 expression was proposed to reflect platelet/macrophage conjugates. However, several studies in reporter mice driven by Pf4-Cre have demonstrated widespread macrophage expression of this gene, notably in peritoneal macrophages 152 and (peri)vascular macrophages 153 . Thus, Pf4 can no longer be considered platelet-specific.…”
Section: Macrophage Subsets In Atherosclerosismentioning
confidence: 99%
“…Similarly, P2Y12 has also been shown to distinguish resident microglia from infiltrated monocytes [25,59]. As such, this marker is also being targeted for the development of genetic tools that can be utilized for the labeling and separation of microglia from monocytes [60]. However, it should be noted that under certain pathological conditions, microglia‐specific markers ( i.e., P2Y12) can be down‐regulated following activation [61,62].…”
Section: Distinguishing Infiltrating Monocytes From Resident Microgliamentioning
confidence: 99%
“…Similarly, P2Y12 has also been shown to distinguish resident microglia from infiltrated monocytes [25,59]. As such, this marker is also being targeted for the development of genetic tools that can be utilized for the labeling and separation of microglia from monocytes [60]. However, it Fig.…”
Section: Distinguishing Infiltrating Monocytes From Resident Microgliamentioning
confidence: 99%